Experimental (OMA) and Numerical (FEM) Modal Analysis of Ball Mill Foundations. (2015) - Wójcicki, Zbigniew; Grosel, Jacek; Sawicki, Wojciech; Majcher, Krzysztof; Pakos, Wojciech
Abstract: The paper presents the results of the modal analysis of a ball mill foundation, an element of the processing technological line in an ore enrichment plant in Poland. The modal analysis was performed in two ways: numerically, using FEM, and experimentally, using OMA. The analyses results were validated and the FEM model was tuned appropriately. The results show a surprisingly good supporting structure design in an era when modern design methods, such as the FEM method, were not yet available, i.e. in the 1960s. The study results ruled out the state of the ground on which the foundation rests as the cause of large structure vibration. Instead, the poor technical condition of the machinery (ball millbearings) was indicated as the main cause.